2022
DOI: 10.1111/ans.17730
|View full text |Cite
|
Sign up to set email alerts
|

Mesh fixation techniques in Lichtenstein tension‐free repair: a network meta‐analysis

Abstract: Backgrounds: To compare the clinical effectiveness of different mesh fixation techniques in Lichtenstein tension-free repair using network meta-analysis. Methods: Cochrane Library, Medline, EMBASE, and Web of Science databases were searched until 1 December 2020, and randomized controlled trials (RCTs) comparing outcomes between different mesh fixation techniques were included. The primary endpoints were chronic postoperative inguinal pain (CPIP) and hernia recurrence. The second endpoint was seroma and infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The current meta-analysis evidence of mesh fixation in OHR suggested that glue was superior to suture mesh at shorter operative time and reduced pain, but had no effect on long-term hernia recurrence, while chronic groin pain was equivocal. For SGM, no difference was found in the use of mesh fixation compared to suture or compared to flat mesh itself [9][10][11][12][13][14][15][16][17][18][19][32][33][34]. In LHR, glue was more useful than tack in reducing chronic groin pain, but there was no difference in hernia recurrence [34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The current meta-analysis evidence of mesh fixation in OHR suggested that glue was superior to suture mesh at shorter operative time and reduced pain, but had no effect on long-term hernia recurrence, while chronic groin pain was equivocal. For SGM, no difference was found in the use of mesh fixation compared to suture or compared to flat mesh itself [9][10][11][12][13][14][15][16][17][18][19][32][33][34]. In LHR, glue was more useful than tack in reducing chronic groin pain, but there was no difference in hernia recurrence [34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 96%
“…For SGM, no difference was found in the use of mesh fixation compared to suture or compared to flat mesh itself [9][10][11][12][13][14][15][16][17][18][19][32][33][34]. In LHR, glue was more useful than tack in reducing chronic groin pain, but there was no difference in hernia recurrence [34][35][36][37][38][39][40]. There is no SGM information for LHR.…”
Section: Discussionmentioning
confidence: 99%
“…In open inguinal hernia operations, especially those utilizing the Lichtenstein method, various studies have suggested that fibrin glue is an effective alternative to sutures in reducing invasiveness [1][2][3][4][5][6] . In endoscopic hernia repair, there is a growing trend towards avoiding invasiveness by not fixing the mesh, as recommended by guidelines from the HerniaSurge Group 7 .…”
Section: Impact Of Different Fibrin Glue Application Methods On Ingui...mentioning
confidence: 99%
“…Therefore, there has been a shift in research focus toward reducing complication rates, which led to an increased interest in less invasive mesh xation methods. More studies have reported the e cacy of brin glue for inguinal hernias in clinical settings [8][9][10][11][12][13][14][15][16]. Further, basic research comparing xation capabilities between brin glue and tacks or staples and studies on meshes that are compatible with brin glue are advancing [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%